Determination of clinical target volume to planning target volume margins and set up errors in image guided radiotherapy for head and neck and prostate cancer patients treated in helical tomotherapy: an institutional study - Bora, Ghritashee; Goswami, Smriti; Baruah, Rheetwik; Das, Kaustav; Goswami, Bibhash C.; Paul, Moumita; Penumur, Manasa (International Journal of Research in Medical Sciences, 2024)
Background: Appropriate immobilization and accurate target delineation is imperative in radiotherapy planning and treatment. To achieve optimum target volume coverage with reduced dose to organs at risk, variability in set up should be minimized. This study was an attempt to determine the translational errors and corresponding planning target volume margins in head and neck and prostate cancer patients treated with helical tomotherapy. Methods: This is a retrospective observational study of a total of 29 patients of head and neck cancer and 7 patients of prostate cancer treated in helical tomotherapy with image guided radiation therapy. The shifts in the translational directions were recorded and the systematic and random errors were calculated to obtain the corresponding clinical target volume (CTV) to planning target volume (PTV) margins using Van Herk formula. Results: A total of 945 CBCT images were acquired for the head and neck region and 237 images for the pelvic region. The corresponding CTV-PTV margins in the X, Y and Z directions were 3.5 mm, 3.7mm and 3.4mm respectively for the head and neck region and 4.4mm,8.7mm and 5.8mm in the prostate cancer patients. Conclusions: Image guided radiation therapy is an effective method for ensuring adequate coverage of the target in IMRT technique. Thus, proper imaging will lead to less chances of geographic miss.